2019
DOI: 10.1177/2472555219830086
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Expression of a CFP-YFP FRET Diacylglycerol Sensor Enables Multiple-Read Screening for Compounds That Affect C1 Domains

Abstract: Intramolecular CFP-YFP fluorescence resonance energy transfer (FRET) sensors expressed in cells are powerful research tools but have seen relatively little use in screening. We exploited the discovery that the expression of a CFP-YFP FRET diacylglycerol sensor (DAGR) increases over time when cells are incubated at room temperature to assess requirements for robust measurements using a Molecular Devices Spectramax i3x fluorescence plate reader. Expression levels resulting in YFP fluorescence >10-fold higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…We also screened the Mechanistic Set for compounds that act as either agonists or antagonists of C1 domains using a multiple read assay based on expression of a FRET reporter for diacylglycerol. 13 We confirmed that 16 compounds demonstrated antagonist activity in the primary screen, a hit rate again of ~2%. All of these compounds also blocked translocation of the sensor from cytosol to membrane as expected when measured using microscopy, which served as an orthogonal assay, but none demonstrated the expected inhibitory effects on activation of protein kinase C (PKC)—in fact, some activated PKC.…”
Section: Our Experience With the Nci Setssupporting
confidence: 62%
“…We also screened the Mechanistic Set for compounds that act as either agonists or antagonists of C1 domains using a multiple read assay based on expression of a FRET reporter for diacylglycerol. 13 We confirmed that 16 compounds demonstrated antagonist activity in the primary screen, a hit rate again of ~2%. All of these compounds also blocked translocation of the sensor from cytosol to membrane as expected when measured using microscopy, which served as an orthogonal assay, but none demonstrated the expected inhibitory effects on activation of protein kinase C (PKC)—in fact, some activated PKC.…”
Section: Our Experience With the Nci Setssupporting
confidence: 62%
“…Second, and related, the requirement that Z' be > 0.5 may lead researchers to conduct assays under conditions that maximize Z' but hinder detection of useful compounds, as has been noted by Glickman 6 and Bray et al 3 As an example of our experience with this, we recently developed a screen for compounds that act as antagonists of phorbol dibutyrate (PDBU) binding to C1 domains. 12 To achieve Z' > 0.5, we conducted the screen with a very high concentration (100 nM) of the activator PDBU. Since the Kd for PDBU binding is in the low nM range, 13 however, we speculate that using PDBU in excess may have prevented us from finding competitive antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…Given the recent advances in synthetic biology, the transcriptional regulator (transcription factor [TF])-based biosensor has emerged as one of the most powerful tools to increase enzyme activity or to discover new enzymes or strains. Various TF-based biosensors have been developed for enzyme engineering and the discovery of novel biocatalysts, using a fluorescence-activated cell sorting (FACS)-based high-throughput screening system [14,15,16,17,18,19,20,21]. Formaldehyde- and formate-dependent TFs have been reported in the operon of formaldehyde detoxification and the expression system of anaerobic formate dehydrogenase, respectively [22,23].…”
Section: Introductionmentioning
confidence: 99%